Teaching Writing Analytical Exposition Text Using YouTube Media Assisted by Whatsapp - Ida Lisdawati; siska rizkiani; angga maulana (International Journal of English Linguistics, Literature, and Education (IJELLE), 2023)
This research aims to describe the responses of teachers and students toward teaching and learning, the challenges that students face when learning writing, and the challenges that teachers face when teaching students through the writing process. This research used descriptive qualitative research to describe or explain systematically and accurately events. The research participants were conducted eleventh-grade students in SMK PGRI 2 Karawang, consisting of 30 students. The instruments of this research are an observation sheet, questionnaire, interviews, and tests. The results showed that the research found three findings. First, the teachers' responses could help students be more active, communicative, effective, and efficient. Second, the questionnaire results showed that most students positively responded to learning to write analytical exposition texts using YouTube as a medium because it made it easier for them to understand the subject matter. Third, this research can be employed as a reference by another researchers conducting further research on senior high school writing instruction for analytical exposition texts.